1998
DOI: 10.1159/000023937
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Lodoxamide on Eosinophil Activation

Abstract: Recent reports describe the beneficial use of lodoxamide, an anti-allergic compound, for the treatment of asthma and allergic conjunctivitis. Lodoxamide is known as a mast cell stabilizer, however, the association of a significant clinical improvement with a specific decrease in eosinophil infiltrate suggested possible direct effects of lodoxamide on eosinophils. The chemotactic response of eosinophils to fMLP as well as to IL-5, in vitro, was very significantly and dose-dependently inhibited by Lodoxamide. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…After the demonstration that drugs like lodoxamide, a potent antiallergic drug, could inhibit several parameters of eosinophil activation including chemotaxis and release of cytotoxic mediators [22], we have recently extended this observation to a new immunosuppressive drug, suplatast tosilate (IPD), shown to specifically inhibit the Th2 immune response [23]. …”
Section: Resultsmentioning
confidence: 99%
“…After the demonstration that drugs like lodoxamide, a potent antiallergic drug, could inhibit several parameters of eosinophil activation including chemotaxis and release of cytotoxic mediators [22], we have recently extended this observation to a new immunosuppressive drug, suplatast tosilate (IPD), shown to specifically inhibit the Th2 immune response [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting the inflammatory influx of eosinophils and/or the release of toxic mediators would allow significant treatment of allergic inflammation. Our previous in vitro studies have shown the usefulness of anti‐allergic drugs by demonstrating that molecules, such as cetirizine or lodoxamide, could have a direct effect on eosinophil functions, allowing better understanding of the drug mechanism (6, 29). In this study, we investigated the effect of ketotifen, a drug with anti‐anaphylactic and antihistaminic properties already used in the treatment of asthma and AC, on eosinophil chemoattraction and on the release of inflammatory mediators, such as ROS, ECP, and EDN by activated eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of leukocyte chemotaxis was assessed by a modification of the Boyden micropore filter technique, as previously described (6). Briefly, the assay is carried out in a 48‐well microchemotaxis assembly (Neuroprobe; Cabin John, MD).…”
Section: Chemotaxis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Lodoxamide was shown to downregulate ICAM-1 expression (both constitutive and IFNγ -stimulated) in a conjunctival epithelial cell line [56]. Capron and coworkers demonstrated in vitro that lodoxomide significantly and dose-dependently inhibited the chemotactic response of human eosinophils to N-formyl methionine leucylphenylalanine (fMLP) and IL-5 [58]. Lodoxamide also inhibited IgA dependent release of eosinophil peroxidase (EPO), eosinophil cationic protein (ECP) and eosinophilderived neurotoxin (EDN).…”
Section: Mast Cell Stabilizers and Dual Action Drugsmentioning
confidence: 99%